Pentingnya Guru Pak Mengajar Dengan Kasih Berdasarkan 1 Korintus 13:4-7 Implikasi Bagi Pertumbuhan Rohani Siswa - Priskila Kompong (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The purpose of Christian Religious education in the family is to teach about human relations with God and His creation. Christian Religious Education can be carried out in families, schools and places of worship without being limited by space and time. real to children, so that children understand the purpose of this life. Christian Religious Education in the family is very important to be applied by parents today. One of the roles of Christian Religion education in the family today is to seek the cooperation of fathers and mothers in educating children as well as creating harmony in the family. Therefore, the family is the most important environment in carrying out the social formation of children. So, the role of parents in raising children is very important, not only do children learn and experience growth in the family, but all family members can learn from each other through interaction with each other. However, all of this cannot be separated from the example of parents. in family.